Isolation, Structural Characterisation and Wound Healing Activity of Flavonoid and its Glycoside from Euphorbia hirta L. Methanolic Extract - Alsaffar, Dania; Maram B. Alhawarri; Ahmed Yaseen; Nur Aziah Hanapi; Siti Rafidah Yusof; Roza Dianita; Nur Hidayah Kaz Abdul Aziz (Iraqi Journal of Pharmaceutical Sciences, 2024)
Euphorbia hirta is a plant belonging to the Euphorbiaceae family that is widely used in traditional medicine to treat various dermal diseases in tropical and subtropical countries. It has been found to have anti-inflammatory and wound-healing effects, which may make it a promising natural treatment for different medical conditions. The aim of the present study focuses on the investigation of the main active compounds associated with the wound-healing activity of plants. The plant powder of aerial part was sequentially extracted with n-hexane, chloroform, methanol, and water using the serial exhaustive extraction method.The extract with the best activities was further fractionated using various chromatographic techniques to isolate the active compounds responsible for wound healing. The isolated compounds were assessed for wound healing activity by measuring migration and proliferation against human dermal fibroblast cells. The structure elucidation of compounds was confirmed by IR, LC-MS, and NMR. These isolated compounds were subsequently identified as kaempferol and its glycoside, kaempferol-3-O-glucoside (astragalin). The findings also revealed that both isolated compounds were able to stimulate the cell population with no sign of toxicity and the highest cell migration ability shows after 48-hour treatment. This study provides new evidence to support the traditional use of E. hirta as a natural promising wound healer.